2018
DOI: 10.5125/jkaoms.2018.44.3.112
|View full text |Cite
|
Sign up to set email alerts
|

Clinical experience in managing temporomandibular joint ankylosis: five-year appraisal in a Nigerian subpopulation

Abstract: ObjectivesTemporomandibular joint ankylosis (TMJA) is a joint pathology caused by bony and/or fibrous adhesion of the joint apparatus, resulting in partial or total loss of function.Materials and MethodsThis is a retrospective study conducted between 2012 and 2016 in the northwest region of Nigeria. The data retrieved includes gender, age, etiology of ankylosis, duration of ankylosis, laterality of ankylosis, type of imaging technique, type of airway management, types of incision, surgical procedure, mouth ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 29 publications
(30 reference statements)
2
17
0
Order By: Relevance
“…In the present study, ankylosis cases were more predominant in females (55.8%) than males (44.2%), with a sex ratio of female to male 1.26:1. This nding is in agreement with other reports from Sudan [2], Morocco [17], South Africa [8], Pakistan [18], and Nigeria [19]. In contrast, studies from Nigeria [5] and India [16] reported the predominance of TMJA cases among males than females.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, ankylosis cases were more predominant in females (55.8%) than males (44.2%), with a sex ratio of female to male 1.26:1. This nding is in agreement with other reports from Sudan [2], Morocco [17], South Africa [8], Pakistan [18], and Nigeria [19]. In contrast, studies from Nigeria [5] and India [16] reported the predominance of TMJA cases among males than females.…”
Section: Discussionsupporting
confidence: 92%
“…Preoperative diagnosis of TMJ ankylosis with the help of CBCT (coronal view) is very important to detect Sawhney type III cases. Although CT is a standard investigative procedure for TMJ ankylosis, clinicians working in resource-scarce environments may rely on plain radiographs alone9. However, plain radiographs alone cannot detect Sawhney type III cases, and as a result, these cases are managed improperly as type IV cases.…”
Section: Discussionmentioning
confidence: 99%
“…However, plain radiographs alone cannot detect Sawhney type III cases, and as a result, these cases are managed improperly as type IV cases. The importance of getting a preoperative CT or CBCT scan cannot be over-emphasized9.…”
Section: Discussionmentioning
confidence: 99%
“…The Journal of Oral and Maxillofacial Surgery (JOMS)45678910111213 was one journal title selected from journals indexed by Scopus and SCIE that was correctly classified as an oral surgery title. (Tables 1, 3) The Journal of the Korean Association of Oral and Maxillofacial Surgeons (JKAOMS)14151617181920212223 was one journal title selected from the journals indexed by Scopus only and was correctly classified as an oral surgery title. (Table 1) One journal title that was selected from journals not indexed by Scopus or SCIE and classified as an oral surgery title was Maxillofacial Plastic and Reconstructive Surgery (MPRS)24252627282930313233.…”
Section: Methodsmentioning
confidence: 99%